Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

kris2685

  • 3 years ago

solve and check 5(y+6) = 5(y-3)

  • This Question is Closed
  1. BurrDaBoss
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    5(y+6=5(y-3) 5y+30=5y-3 5y+30+3=5y-3+3 5y+33=5y 5y+33-5y=5y-5y y=33

  2. kelsey1
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    5(y+6)=5(y-3) 5y+30=5y-15 +15 +15 5y+45=5y -5y -5y 45=y

  3. BurrDaBoss
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Sorry , she's right I made a mistake somewhere.

  4. kris2685
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    thank you kelsey

  5. kelsey1
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    No problem once you get "y" you can plug it back in to see if you got the right answer they should equal each other.

  6. kelsey1
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 2

    I was wrong. The y's cancel out, so that means that 45=0 which is FALSE so the answer is, NO SOLUTION.

  7. ChmE
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    @BurrDaBoss 's mistake comes from not distributing correctly.

  8. ChmE
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    5(y+6)=5(y-3) 5y+30=5y-15 add 15 to both sides 5y+45=5y subtract 5y from both sides 45 = 0 impossible no solution @kelsey1 was right

  9. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy